Limonene monitoring in citrus industry wastewater using molecularly imprinted voltammetric sensor - Zancan, Aléxia Massinatore [UNESP]; da Silva, José Luiz [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2025)
The present work reports the development of a novel molecularly imprinted polymer (MIP) electrochemical sensor for limonene determination in orange industry wastewater. MIP sensor was constructed through the pyrrole electropolymerization in the presence of limonene on glassy carbon electrode surface (GCE/MIP). Electrode surface as characterized by electrochemical, spectroscopy and microscopic techniques. The analysis was performed using differential pulse voltammetry, employing hexacyanoferrate as the electrochemically active probe. Under optimized conditions, the proposed GCE/MIP sensor displayed linear range from 1.0 to 100 pmol L−1 with a high sensitivity (0.92 nA L pmol−1) and low detection limit (0,87 pmol L−1), as well as excellent storage stability, repeatability and reproducibility. The imprinted factor found for the sensor was 4.1 with high selectivity. The applicability of the sensor was successfully evaluated by limonene determination in yellow water sample. GCE/MIP showed recovery from 97 to 105 %. The results, altogether, indicate that the GCE/MIP sensor can provide a sensitive and selective method for limonene determination with accuracy and precision.
Keywords: Agroindustry residues; Electrochemical sensor; Environmental analysis; Limonene detection; MIP electropolymerization; Molecularly imprinted polymers